2014
DOI: 10.1002/hfm.20556
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Relationship Between Green Consumption Value, Satisfaction, and Loyalty to Hybrid Car in Elderly Consumers

Abstract: The study aimed to examine the relationship between green consumption value, satisfaction, and loyalty of driving hybrid cars among elderly consumers. Data were collected from a cross-sectional survey of 314 elderly consumers who purchased hybrid cars in the United States. A partial least squares analysis revealed that elderly consumers' social, price, and quality values positively influenced the satisfaction of their hybrid car experience, and their satisfaction significantly influenced their loyalty of hybri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 55 publications
(79 reference statements)
0
18
1
Order By: Relevance
“…On the contrary, the more the purchase is driven by social acceptance desire, the lower the satisfaction deriving from it. This result is in contrast with the study on hybrid cars by W. M. Hur et al (2015), and this may depend on the specific category of product under investigation. In our study, green products are considered as a broad category; actually, as our survey highlights (Table 3), respondents buy green products belonging to a wide variety of goods.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…On the contrary, the more the purchase is driven by social acceptance desire, the lower the satisfaction deriving from it. This result is in contrast with the study on hybrid cars by W. M. Hur et al (2015), and this may depend on the specific category of product under investigation. In our study, green products are considered as a broad category; actually, as our survey highlights (Table 3), respondents buy green products belonging to a wide variety of goods.…”
Section: Discussioncontrasting
confidence: 99%
“…Further, the study by W. M. Hur et al (2015) on product satisfaction for hybrid cars showed that social value positively influences the satisfaction of consumers' hybrid car experience and their satisfaction, in turn, significantly influences their loyalty to hybrid cars' category.…”
Section: Social Valuementioning
confidence: 98%
“…Furthermore, it is widely recognized that many symbols might be used for social stratification in various cultures (Bourdieu, ; Holt, ). Specifically, the status value of green consumption has been highlighted in different countries and cultures (in the UK by Tapp and Warren, ; in the US by Hur et al ., ). Thus, it may be fruitful to conduct the same analysis as in our study in other parts of France and in other countries.…”
Section: Discussionmentioning
confidence: 97%
“…Yet why people buy organic food and how venue affects their choice is not totally understood. Green consumption practices have been related to social classes and status (Griskevicius et al ., ; Hur et al ., ; Tapp and Warren, ). Some researchers recognize that food is an expression of identity and values (Senauer, ), while others see it as reflecting lifestyle (Brunsø et al ., ).…”
Section: Introductionmentioning
confidence: 99%
“…Even if individuals exhibit different forms of behaviour, they have the value of society as a member (Kuzudişli, 2017). Marketers, on the other hand, must be sufficiently aware of the value dimensions that exist in the consumer's decision to adopt green products in order to meet increasing social demands (Hur et al, 2015). Social values are one of the most effective ways of reducing the negative effects of consumption on the environment and of sustainability, especially in terms of perpetuating consumption values (Yadav & Pathak, 2017).…”
Section: Introductionmentioning
confidence: 99%